The effects of organizational responses to complaints on satisfaction and loyalty: A study of hotel guests in Northern Cyprus - Karatepe, Osman M.; Ekiz, Erdogan Haktan (My University, 2004)
This study investigates the effects of various organizational responses to complaints on post-complaint customer behaviors. Specifically, the study investigates the effects of apology, atonement, promptness, facilitation, explanation, attentiveness and effort on complainant satisfaction and loyalty, and the association between satisfaction and loyalty. The study uses a sample of Turkish guests in the Northern Cyprus hotel industry. The hypothesized relationships are tested using LISREL 8.30 through path analysis. Results provide empirical support for ten of the 15 hypotheses examined. The path analysis reveals that apology, explanation, and effort are three organizational response options that exert significant positive effects on complainant satisfaction and loyalty. Empirical findings also suggest that effort appears to be the most influential organizational response affecting satisfaction and loyalty. Discussion of the results, implications, and limitations of the study are also presented. © 2004, Emerald Group Publishing Limited
Keywords: Complaints; Customer loyalty; Customer satisfaction; Cyprus; Organizational behaviour